2018
DOI: 10.2147/jpr.s144631
|View full text |Cite
|
Sign up to set email alerts
|

Current status of acceptance and commitment therapy for chronic pain: a narrative review

Abstract: It is well known that chronic pain is prevalent, complex to manage, and associated with high costs, in health care and society in general. Thanks to advances in new forms of cognitive behavioral therapy (known as third-wave CBT), currently clinicians and researchers have an empirically validated psychological treatment with increasing research support for the treatment of chronic pain. This treatment is called acceptance and commitment therapy (ACT). The main aim of this paper is to provide a narrative review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
108
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 108 publications
1
108
0
3
Order By: Relevance
“…The research on the effect of ACT as a therapy for mood disorders confirmed it as an effective treatment for mood, anxiety, and other psychological disorders such as pain and eating disorder (15,16). The ACT is used for treating anger (17), chronic pain, drug abuse, and many other problems as well (18,19). Further, it is an effective therapy for decreasing infertility stress, psychological distress, and infertility-related depression (20), as well as a promising treatment for patients who have failed in vitro fertilization.…”
mentioning
confidence: 95%
“…The research on the effect of ACT as a therapy for mood disorders confirmed it as an effective treatment for mood, anxiety, and other psychological disorders such as pain and eating disorder (15,16). The ACT is used for treating anger (17), chronic pain, drug abuse, and many other problems as well (18,19). Further, it is an effective therapy for decreasing infertility stress, psychological distress, and infertility-related depression (20), as well as a promising treatment for patients who have failed in vitro fertilization.…”
mentioning
confidence: 95%
“…Many different forms of acceptance-based programs were developed and tested for effectiveness. They were shown to be successful in stress and pain reduction as well as decreasing anxiety and depression symptoms (Segal et al, 2002;Hayes et al, 2006;Veehof et al, 2011;Twohig and Levin, 2017;Feliu-Soler et al, 2018). Other studies showed the role of mindfulness and acceptance for the severity of psychotic symptoms (Cramer et al, 2016;Jansen et al, 2019), eating disorders (Prefit et al, 2019), compulsive sexual behavior (Lew-Starowicz et al, 2019), addictive behaviors (Bowen et al, 2011), suicidal ideation and self-harm (Tighe et al, 2018) as well as other psychopathological symptom clusters (Aldao et al, 2010).…”
mentioning
confidence: 99%
“…Similarly, higher PF has also been found to be associated with less pain intensity and interference, less anxiety and depressive symptomatology, and improved physical and mental functioning in patients with FM [17,23,24]. Furthermore, PF (and its individual components) have also been reported to mediate clinical changes in acceptance-and mindfulness-based interventions delivered to patients with chronic pain [22,25] and FM [26][27][28].…”
Section: Introductionmentioning
confidence: 92%
“…Although PF has been established as a relevant transdiagnostic mechanism and as a key variable in explaining the effects of third-wave cognitive behavioral interventions on health, studies assessing the brain structures underpinning this set of cognitive processes are lacking [25]. The main objective of the present study was to explore the brain structural correlates of PF, as measured by the Psychological Inflexibility in Pain Scale (PIPS) [24] in patients with FM.…”
Section: Introductionmentioning
confidence: 99%